2020
DOI: 10.1038/s41467-020-16970-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing trends in regional heatwaves

Abstract: Heatwaves have increased in intensity, frequency and duration, with these trends projected to worsen under enhanced global warming. Understanding regional heatwave trends has critical implications for the biophysical and human systems they impact. Until now a comprehensive assessment of regional observed changes was hindered by the range of metrics employed, underpinning datasets, and time periods examined. Here, using the Berkeley Earth temperature dataset and key heatwave metrics, we systematically examine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
524
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 941 publications
(557 citation statements)
references
References 33 publications
26
524
1
6
Order By: Relevance
“…As a consequence, Sweden experienced a very long warm period with an unusually high number of warm days. Similar pressure patterns to those observed in summer 2018 have previously been shown to be associated with warm temperature anomalies over different parts of Europe (Sousa et al, 2018;Zschenderlein et al, 2019); for example, Pfahl and Wernli (2012) found that most summer heatwaves (80 %) in northern Europe and Russia can be associated with atmospheric blocking situations. Sinclair et al (2019) concluded that the 2018 heatwave was not intensified by surface feed-R. A. I.…”
Section: Introductionsupporting
confidence: 82%
“…As a consequence, Sweden experienced a very long warm period with an unusually high number of warm days. Similar pressure patterns to those observed in summer 2018 have previously been shown to be associated with warm temperature anomalies over different parts of Europe (Sousa et al, 2018;Zschenderlein et al, 2019); for example, Pfahl and Wernli (2012) found that most summer heatwaves (80 %) in northern Europe and Russia can be associated with atmospheric blocking situations. Sinclair et al (2019) concluded that the 2018 heatwave was not intensified by surface feed-R. A. I.…”
Section: Introductionsupporting
confidence: 82%
“…Another reasonable result of the temperature increase is expanding the areas suitable for viticulture to areas with higher altitudes, where the temperatures for vines are currently too low [ 22 ]. Besides the rise of the mean annual temperature, heatwaves during the crucial development stages of grape berry have increased in the last decades, and under enhanced global warming they are expected to worsen, becoming more frequent and more intense [ 30 , 31 ]. These prolonged periods of excessive heat events may have dramatic impacts on both the quality and the yield of grape production, despite the overall suitable weather conditions [ 13 , 31 ].…”
Section: Global Warming Impacts On Grapevine Phenology and Viticulmentioning
confidence: 99%
“…As greenhouse gas concentrations continue to rise, regional warming will intensify [•• 11 , 16 ]; models suggest that alterations in atmospheric dynamics may lead to large changes in precipitation, particularly in subtropical and mid-latitude regions. [ 17 19 ].…”
Section: Climate Change Hazards: Drought Heat Sea-level Rise and Smentioning
confidence: 99%